Morphology of Sea Cucumber (Holothuridea) Types on Sembilan Island, Sinjai Regency: Study of Their Potential in the Aquatic Industry - Sitti Fatimah (Tinta Emas Institute, 2025)
Morphology of sea cucumber species (Holothuridea) in Pulau Sembilan, Sinjai Regency. The purpose of this study is to find out what types of sea cucumbers are found on Pulau Sembilan, Sinjai Regency. The research was carried out from April to May 2024 in Pulau Sembilan, Sinjai Regency. Data were collected through interviews and direct observation using purposive sampling techniques. The research location includes three islands, namely Kambuno Island, Batanglampe Island and Kanalo I Island. The results of the study showed that there were 9 types of sea cucumbers at three locations research. Types of sea cucumbers that have been successfully identified based on morphology such as shapes, colors and patterns including Spotted Sea Cucumber (Bohadschia Ocellata), Mock sea cucumber or plain sea cucumber (Bohadschia Vitiensis), Black Sea Cucumber or Lotong Sea Cucumber (Holothuria Atra), Peanut Sea Cucumber (Stichopus Horren), Black Cera Sea Cucumber or Lotong Cera Sea Cucumber (Holothuria Leucospilota), Silk Sea Cucumber or Blind Sea Cucumber (Pearsonothuria Graeffei), Stone Sea Cucumberor Kapo Sea Cucumber (Actinophyga Lecanora), Rubber Sea Cucumber Spotted or Kawasa Sea Cucumber (Bohadschia Similis) and Gamet Sea Cucumber (Stichopus Vastus).